(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
In the Tashkent and Syrdarya regions, the following species of Rhipicephalus ticks were found: R. sanguineus, R. turanicus, R. bursa, R. pumilio species, a wide distribution of R. sanguineus species in domestic animals was noted. In particular, the damage rate (IE) of agricultural animals was: Bos taurus 38%, Ovis aries 50.6%, Capra hircus 41.8%, Equus caballus 38.1%, Canis lupus familiaris 54.5%.